Integrated value–based project management in the Malaysian construction industry / Mohd Hilmi Malek and Che Maznah Mat Isa - Malek, Mohd Hilmi; Mat Isa, Che Maznah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2024)
Value Management (VM) is a structured approach to maximising a project’s value by analysing its functions, materials, and costs to meet objectives at the lowest cost without compromising quality, performance, or functionality. In Malaysia’s construction industry, VM has significantly enhanced project outcomes. However, VM faces challenges despite its benefits due to limited awareness, knowledge barriers, and a gap between theory and practice. Although many practitioners recognise VM’s advantages, there remains a need for a deeper understanding of the VM process and how to apply necessary project management (PM) activities for project success. This study addresses the gap in understanding how PM activities can be integrated with VM to enhance project performance in the Malaysian construction industry. PM involves planning, organising, and controlling resources to achieve specific goals within set constraints, using knowledge, skills, tools, and techniques to successfully execute projects and deliver desired outcomes. The study employed a qualitative method, including interviews with eleven professionals and practitioners in Malaysia’s construction industry, to identify PM activities that can be incorporated into the VM process. Thematic analysis using Atlas.ti revealed that PM and VM share similar objectives in ensuring project performance. The study illustrates the benefits of incorporating PM operations into VM by highlighting the relationships between PM and VM, such as better collaboration, better resource management, and improved project outcomes. By providing practitioners with a framework to apply PM techniques within the VM process, our findings contribute to the innovation of VM concepts, enhancing project performance, and bridging the theory-practice gap in the Malaysian construction sector.